Four-Octyl itaconate ameliorates periodontal destruction via Nrf2-dependent antioxidant system - Liangjing Xin; Fuyuan Zhou; Chuangwei Zhang; Wenjie Zhong; Shihan Xu; Xuan Jing; Dong Wang; Si Wang; Tao Chen; Jinlin Song (Nature Publishing Group, 2022)
Abstract Periodontitis is a widespread oral disease characterized by continuous inflammation of the periodontal tissue and an irreversible alveolar bone loss, which eventually leads to tooth loss. Four-octyl itaconate (4-OI) is a cell-permeable itaconate derivative and has been recognized as a promising therapeutic target for the treatment of inflammatory diseases. Here, we explored, for the first time, the protective effect of 4-OI on inhibiting periodontal destruction, ameliorating local inflammation, and the underlying mechanism in periodontitis. Here we showed that 4-OI treatment ameliorates inflammation induced by lipopolysaccharide in the periodontal microenvironment. 4-OI can also significantly alleviate inflammation and alveolar bone loss via Nrf2 activation as observed on samples from experimental periodontitis in the C57BL/6 mice. This was further confirmed as silencing Nrf2 blocked the antioxidant effect of 4-OI by downregulating the expression of downstream antioxidant enzymes. Additionally, molecular docking simulation indicated the possible mechanism under Nrf2 activation. Also, in Nrf2−/− mice, 4-OI treatment did not protect against alveolar bone dysfunction due to induced periodontitis, which underlined the importance of the Nrf2 in 4-OI mediated periodontitis treatment. Our results indicated that 4-OI attenuates inflammation and oxidative stress via disassociation of KEAP1-Nrf2 and activation of Nrf2 signaling cascade. Taken together, local administration of 4-OI offers clinical potential to inhibit periodontal destruction, ameliorate local inflammation for more predictable periodontitis.